2023
DOI: 10.1038/s41598-023-41594-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of workplace bullying and burnout with nurses’ suicidal ideation in Bangladesh

Humayun Kabir,
Saifur Rahman Chowdhury,
Anjan Kumar Roy
et al.

Abstract: Suicidal ideation is a complex phenomenon influenced by several predisposing, contextual, and mediating factors that seem more common among healthcare workers, especially nurses. We investigated the association of bullying and burnout with suicidal ideation among Bangladeshi nurses and identified the associated factors. We conducted a cross-sectional study among 1264 nurses in Bangladesh between February 2021 and July 2021. We applied a modified Poisson regression model with robust error variance to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Regarding sociodemographic factors, our results found no statistically significant differences in the scores of suicidal ideation due to sex, type of work sector, age, and years of experience, while the monthly income variable was statistically significant (income under 500 JD (1,057 $)). Low income and economic inequalities could be potential predictors of suicidal ideation among healthcare professionals, owing to their negative effects on their quality of life and impeding career advancement (48). Kabir et al (48) found that monthly income, geographical location of the workplace, department of work, and insufficient equipment to manage patients were associated with suicidal ideation among nurses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding sociodemographic factors, our results found no statistically significant differences in the scores of suicidal ideation due to sex, type of work sector, age, and years of experience, while the monthly income variable was statistically significant (income under 500 JD (1,057 $)). Low income and economic inequalities could be potential predictors of suicidal ideation among healthcare professionals, owing to their negative effects on their quality of life and impeding career advancement (48). Kabir et al (48) found that monthly income, geographical location of the workplace, department of work, and insufficient equipment to manage patients were associated with suicidal ideation among nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Low income and economic inequalities could be potential predictors of suicidal ideation among healthcare professionals, owing to their negative effects on their quality of life and impeding career advancement (48). Kabir et al (48) found that monthly income, geographical location of the workplace, department of work, and insufficient equipment to manage patients were associated with suicidal ideation among nurses. And nurses in the higher-and middle-income groups showed higher levels of suicidal ideation than those in the lower-income category.…”
Section: Discussionmentioning
confidence: 99%
“…In an Italian prospective study, 48 targets of workplace bullying exhibited increased scores on the MMPI-2 scale's Hs, D, Hy, and Pa items 22 months later, along with high rates of suicidality 7 . Numerous studies have demonstrated that individuals exposed to workplace bullying have increased rates of mental health disorders such as depression, anxiety, leading to suicide 3,4,[40][41][42] . According to the Stress as Offense to Self (SOS) perspective, a theory within workplace bullying, self-worth comprises self-esteem and social esteem.…”
Section: Discussionmentioning
confidence: 99%